EFISIENSI PENGERINGAN TEMBAKAU DENGAN METODE JANTUR (GANTUNG) DI DALAM GREEN HOUSE DIKOMBINASIKAN DENGAN PENAMBAHAN KALSIUM KARBIDA (CaC₂) - Leader Firstandika; Muhammad Arga Hita; Miftahul Choiron; Andrew Setiawan Rusdianto; Winda Amilia (JURNAL REKAYASA SISTEM INDUSTRI, 2026)
This study evaluates the drying efficiency of tobacco (Nicotiana tabacum L.) using the traditional hanging (jantur) method combined with calcium carbide (CaC₂) as an acetylene-generating accelerator. Motivated by common challenges in smallholder postharvest handling—long drying times, weather dependence, and uneven quality—we conducted an experimental trial comparing three treatments: control jantur without CaC₂, jantur with 100 g CaC₂ per chamber, and jantur with 200 g CaC₂ per chamber. Each treatment used randomized placement of 100 sticks, and monitoring included periodic moisture measurements, temperature and relative humidity logging, organoleptic grading, and economic cost analysis. Data collection occurred three times daily to capture drying dynamics and to construct drying curves for each treatment. Results show that all jantur treatments reduced drying time relative to conventional sun drying, achieving final moisture contents near industry targets within approximately 12 days. Average drying rates were close across treatments (≈5.65–5.79% per day), and ANOVA produced non-significant differences (F = 0.3009, p = 0.7421). However, grading outcomes favored the 200 g CaC₂ treatment, which yielded the highest proportion of Grade B leaves (90%) and no Grade C, while 100 g produced mixed results with reduced Grade D but higher Grade C share. Economic assessment indicates substantial cost savings per cycle for jantur treatments compared to sun drying, even after allocating greenhouse investment and CaC₂ costs. In conclusion, integrating CaC₂ into jantur drying offers practical benefits for smallholders by shortening drying cycles and improving grading consistency at modest additional input cost. Although statistical differences in drying rate were not significant, quality and economic indicators support trial adoption, particularly at the 200 g dosage. We recommend larger-scale trials, residue analysis, and safety assessments to validate these findings and ensure safe field application. Further outreach and farmer training on safe CaC₂ handling and ventilation practices should accompany extension of this technique to communities.